POLA ASUH LONG DISTANCE DALAM PEMBENTUKAN KONSEP DIRI REMAJA (Studi Diskriptif Tentang Pola Asuh Long Distance Dalam Pembentukan Konsep Diri Remaja di SMAN 1 Girimarto, Kabupaten Wonogiri) - Retno Wahyu Wulandari; RB Soemanto; Drajat Tri Kartono (UNIVERSITAS SEBELAS MARET (UNS), 2013)
This study was a descriptive qualitative trying to describe the actual condition of informants. This study aimed to find out the long distance caring pattern in the adolescents in SMA Negeri 1 Girimarto, the establishment of adolescent self-concept in SMA Negeri 1 Girimarto, and the relationship of long distance caring pattern applied to the establishment of adolescent self-concept in SMA Negeri 1 Girimarto. Considering the data obtained, it could be concluded that: caring pattern was divided into two: controlled and free. There were two self-concepts established: dynamic and static. Parent provided reward in the form of material or praise for the achievement the adolescents reached as the form of reward and punishment for the fault or infringement they did. The primary family’s attention contributed to the establishment of adolescent self-concept as well, because the adolescents needed environment as a role model. The adolescents living separately from the parents were accustomed to cope with their problems independently. Keywords: Long distance caring pattern, self-concept, adolescent